Toward a New Adequacy in Public School Finance: Analytical and Political Issues - Michael F. Addonizio (Educational Considerations, 2004)
Efforts to improve the fairness and quality of our public education system through school finance reform date back to the dawn of the twentieth century with the work of Cubberly and others.